A new amphipod species from the Indian Ocean (Crustacea: Amphipoda: Lysianassoidea: Podoprionidae) - Horton, Tammy (Zootaxa, 2005)
A new species of the genus Podoprion is described. The species can be distinguished from the other species in the genus, Podoprion bolivari Chevreux, 1891, P. ruffoi Lowry & Stoddart, 1996, and P. mediterraneum Kaim-Malka, 2004, by the shape of gnathopod 2 propodus, coxa 4, number and size of serrations on pereopod 5 basis, and characters of the mouthparts. Material was collected by baited trap at 1185 m off the coast of Pakistan in the northern Arabian Sea.